Progress, challenges and the need to set concrete goals in the global tobacco endgame - Chris Bostic; Eduardo Bianco; Marita Hefler (Pan American Health Organization, 2022)
The tobacco endgame is rapidly moving from aspirational and theoretical toward a concrete and achievable goal and, in some cases, enacted policy. Endgame policies differ from traditional tobacco control measures by explicitly aiming to permanently end, rather than simply minimize, tobacco use. The purpose of this paper is to outline recent progress made in the tobacco endgame, its relationship to existing tobacco control policies, the challenges and how endgame planning can be adapted to different tobacco control contexts. Examples of implemented policies in three cities in the United States and national policies in the Netherlands and New Zealand are outlined, as well as recent endgame planning developments in Europe. Justifications for integrating endgame targets into tobacco control policy and the need to set concrete time frames are discussed, including planning for ending the sale of tobacco products. Tobacco endgame planning must consider the jurisdiction-specific tobacco control context, including the current prevalence of tobacco use, existing policies, implementation of the World Health Organization's Framework Convention on Tobacco Control, and public support. However, the current tobacco control context should not determine whether endgame planning should happen, but rather how and when different endgame approaches can occur. Potential challenges include legal challenges, the contested role of e-cigarettes and the tobacco industry's attempt to co-opt the rhetoric of smoke-free policies. While acknowledging the different views regarding e-cigarettes and other products, we argue for a contractionary approach to the tobacco product market. The tobacco control community should capitalize on the growing theoretical and empirical evidence, political will and public support for the tobacco endgame, and set concrete goals for finally ending the tobacco epidemic.